Pemanfaatan Materi Sejarah Poetri Mardika Dalam Memajukan Status Wanita Untuk Menumbuhkan Nilai Karakter Peserta Didik - Inayati, Wilda Risa (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
This study discusses the utilization of historical material from the Poetry Mardika organization. This material can be implemented to foster character development in students. The introduction addresses education as a learning process intended to help individuals develop the skills, knowledge, and attitudes necessary for success in life. Education typically consists of teaching and learning activities guided by teachers or instructors, involving students in acquiring the skills, knowledge, and values needed to achieve educational goals. Education empowers women to achieve equality with men, which is considered essential. However, education is not only important for women; men also need education. Education is a learning process intended to help individuals develop the skills, knowledge, and attitudes necessary for success in life. It typically consists of teaching and learning activities guided by teachers or instructors, involving students in acquiring the skills, knowledge, and values necessary to achieve educational goals. The values derived from the Poetry Mardika organization can be applied to students. By implementing the Poetri Mardika material in character building, it is hoped that students will develop a sense of nationalism, a spirit of togetherness, and honesty. It can help them become individuals with strong character, responsibility, and care for their surroundings. This research employs a qualitative method with a literature study approach.